POLITICAL WILL PEMERINTAH KABUPATEN KEPULAUAN MERANTI DALAM PENGEMBANGAN PERKEBUNAN SAGU RAKYAT TAHUN 2010-2020 - Alyf Valencia Erel; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The local government of the Meranti Islands Regency is responsible for the development of sago plantations in the area, the problem of this research is the local government's commitment to the development of sago plantations in 2010-2020. The Meranti Archipelago Regency, which is one of the largest sago producers in Indonesia, still lacks plantation development. This study aims to find out how the implementation of the Meranti Islands Regency government's commitment to the development of people's sago plantations in 2010-2020, and to find out what are the inhibiting factors of the government. The research approach used is an approach approach and this type of research is descriptive. The location of this research was conducted in Meranti Archipelago Regency, data collection was done by interview and documentation. The results of this study are that first, the implementation of the commitment to developing sago plantations has not been maximized, it can be seen from the administrative coordination and policy coordination that has not been successful, so that there is still sago produced that has not been maximized. rejected due to lack of clarity and too large a budget. Environmental policies and external environmental policy programs for the development of smallholder sago plantations are legally weak, stemming from the bupati's regulations regarding the main duties and functions as well as a description of the duties of the forestry and plantation service of the Meranti Islands Regency. There are no local regulations on sago conservation and management. Keywords: Initiative, Priority, Mobility, Law Enforcement and Constitution